Gambaran Pet Attachment pada Pemilik Kucing di Karawang: Analisis Statistik Deskriptif - Yolanda Alvinly Salim; Nita Rohayati; Anggun Pertiwi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
In the modern era, keeping pets is no longer merely a recreational activity but is also considered to provide significant psychological benefits. Interactions between humans and pets can foster feelings of happiness, a sense of belonging, and improved overall quality of life. One concept that explains this phenomenon is attachment, an emotional bond typically formed between individuals, but which can also occur between pet owners and their animals. This study aims to describe the emotional attachment between cat owners and their pets in the Karawang region. The research employed a quantitative descriptive method with an incidental sampling technique. A total of 110 cat owners residing in Karawang, aged between 18 and 40 years, participated in this study. The instrument used to measure attachment was the Lexington Attachment to Pets Scale (LAPS). Data analysis included descriptive statistics, cross-tabulation analysis, and an independent samples t-test to identify differences in attachment levels based on gender. The findings revealed that the majority of respondents exhibited a high level of emotional attachment to their cats. Specifically, 98 respondents (89.1%) were categorized as having a high attachment level, while the remaining participants showed a moderate level of attachment. Further analysis on gender differences provided additional insights into patterns of pet attachment among cat owners in Karawang. These findings emphasize that cats are not only pets but also serve as an important source of emotional support and psychological well-being for their owners.